2021
DOI: 10.3390/ijms22158169
|View full text |Cite
|
Sign up to set email alerts
|

Luseogliflozin, a SGLT2 Inhibitor, Does Not Affect Glucose Uptake Kinetics in Renal Proximal Tubules of Live Mice

Abstract: Proximal tubules (PTs) take up most of the glucose in the glomerular filtrate and return it to peritubular capillary blood. Sodium-glucose cotransporter 2 (SGLT2) at the apical membrane takes up glucose into the cell. Glucose then flows across the cells and is transported to the interstitium via glucose transporter 2 (GLUT2) at the basolateral membrane. However, glucose transport under SGLT2 inhibition remains poorly understood. In this study, we evaluated the dynamics of a fluorescent glucose analog, 2-NBDG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Therefore, SGLT2 inhibitors may reduce glucose concentrations in the tubular cells and interstitial space in this area. However, a detailed study showed that, in normal mice, even when glucose reabsorption was inhibited by an SGLT2 inhibitor, glucose concentrations in the S1 segment proximal tubular cells remained relatively constant because glucose flowed in from the interstitial side via glucose transporter type 2 (GLUT2) ( 35 , 36 ). Interestingly, this compensatory response does not work well in damaged kidneys because GLUT2 expression and function are impaired.…”
Section: Sglt2 Inhibitor-induced Reduction In Renal Tubulointerstitia...mentioning
confidence: 99%
“…Therefore, SGLT2 inhibitors may reduce glucose concentrations in the tubular cells and interstitial space in this area. However, a detailed study showed that, in normal mice, even when glucose reabsorption was inhibited by an SGLT2 inhibitor, glucose concentrations in the S1 segment proximal tubular cells remained relatively constant because glucose flowed in from the interstitial side via glucose transporter type 2 (GLUT2) ( 35 , 36 ). Interestingly, this compensatory response does not work well in damaged kidneys because GLUT2 expression and function are impaired.…”
Section: Sglt2 Inhibitor-induced Reduction In Renal Tubulointerstitia...mentioning
confidence: 99%
“…Thus, empagliflozin can ameliorate FFA-induced renal tubular injury via the PPARγ/CD36 pathway [ 12 ] ( Figure 1 ). Nevertheless, an interesting and provocative study by Zhang et al suggested that blood glucose levels per se do not alter glucose influx or efflux kinetics in renal proximal tubules since the SGLT2 inhibitor luseogliflozin was not found to exert significant effects on glucose influx parameters under any level of blood glucose concentration [ 13 ]. The authors speculated that this was because glucose influx occurs through basolateral GLUT2, which is not a direct target of SGLT2 inhibitors [ 13 ].…”
mentioning
confidence: 99%